A Rare Case of Posttraumatic Bilateral BPPV Presentation - Maslovara, Sinisa; Kosec, Andro; Pajic Matic, Ivana; Sestak, Anamarija (Case Reports in Otolaryngology, 2021)
A rare case of a 38-year-old female patient who developed benign paroxysmal positional vertigo (BPPV) three weeks after head trauma is presented. The disease manifested bilaterally, which is not uncommon posttraumatically, but in this case, it manifested itself as canalithiasis of the posterior canal on both sides and cupulolithiasis of the right lateral canal, which to our knowledge is a unique and, until now, unpublished case. The aim of this review is to point out the fact that, in such a complex multicanal and bilateral clinical presentation of BPPV, it is not sufficient to perform only positioning but also additional laboratory tests. With a good knowledge of the etiopathogenesis, pathophysiology and clinical forms of BPPV, we can, in most cases, make an accurate and precise diagnosis of the disease and carry out appropriate treatment.